Residuals of the Archive and the Conflict of the Bananeras in Colombia: Figurations of Violence and Counter-memory in Literature and Photography - Liliana Gómez (Iberoamericana. América Latina - España - Portugal, 2019)
The paper discusses the relationship between literature and a series of photographic images from the United Fruit Company archive. It examines these media as residuals that speak to us about the (in)visibility of the banana massacre in 1928, retold by García Márquez in Cien años de soledad. It discusses how literature conceptualizes crisis and violence while examining how photography appears to be a layer of self-reflection of a literary mediality, as a counterpart against which literature demarcates its own limitations and possibilities. Also, as an alternative semantic of the photography, literature operates as a critical work of remembrance in and of itself. Finally, it proposes that these images, read against the backdrop of the recent initiatives to condemn the crimes against humanity committed by Chiquita, function as counter-discourse of oblivion in order to contest the amnesia of the official narrative.